A Control chart design for monitoring autocorrelated process with multiple exogeneous inputs under model uncertainty. - Poblador, Ma. Sofia Criselda A. (University of the Philippines, 2012)
Abstract (The AR-Sieve Bootstrap is proposed for the construction of a control chart of an autocorrelated process influenced by multiple exogenous inputs. The resulting control charts are compared with EWMA control chart through a simulation study. The AR-Sieve bootstrap control limits are narrower than EWMA control limits. While the proposed method yields a higher rate of false alarms, it is quick in detecting even minimal structural changes).